Effects of LaB6 on the microstructures and ablation properties of 3D C/C-SiC-ZrB2-LaB6 composites. Issue 8 (July 2020) - Fang, Cunqian; Huang, Boyun; Yang, Xin; He, Kejian; Chen, Lei; Shi, Anhong; Zhang, Ze; Huang, Qizhong
Abstract: Cf /LaB6 preform was used to prepare LaB6 doping C/C-ZrC-SiC composites by precursor infiltration and pyrolysis method, and effects of LaB6 on the microstructure and ablation resistance of C/C-SiC-ZrB2 -LaB6 composites were investigated. Results show that LaB6 was reacted with Zr-precursor or its products to generate ZrB2 and other compounds. Thanks to the reactive sintering effect of LaB6, a compact ceramic skeleton was established in the substrate, which played a vital role in densifying and resisting ablation. The oxidation of the evenly-distributed La- and Zr-compounds produced the homogeneous oxide scale. The ternary phases of La2 Si2 O7, La0.71 Zr0.29 O1.65 and La2 Zr2 O7 were participated in the formation of the oxide scale, evolving the layer from SiO2 to SiO2 -La2 Si2 O7 and then to SiO2 -La2 Si2 O7 -La0.71 Zr0.29 O1.65 -La2 Zr2 O7 -ZrO2 layer. After plasma ablation for 360 s, the mass and linear ablation rates were 0.3848 mg/s and 0.3694 μm/s, respectively. The seamless multi-phase layer can effectively prevent the composites from long-time ablation.